Femoral hernia containing the right fallopian tube: chronic pain with menstruation - Marcos-Santos, P (Ann R Coll Surg Engl, 2019)
Femoral hernias represent less than 10% of groin hernias and appear mainly in adult women; incarceration is more usual than in other hernias. Content found within the sac is commonly small bowel or omentum. Other anatomical structures, such as appendix, bladder, Meckel’s diverticulum, ectopic testis, stomach and gynaecological organs are extremely unusual. A 48-year-old woman presented with intense right groin pain over 48 hours. Her past medical history revealed periodical moderate right groin pain coincident with her menstrual cycles, usually self-limited. No abdominal symptoms or fever were present. On physical examination, an incarcerated right femoral hernia was suspected. Subsequently abdominal ultrasound revealed a right femoral hernia containing an echogenic structure with conserved vascularisation. The patient underwent an emergency surgery. During the procedure the right fallopian tube and several small cysts were discovered as the hernia sac contents. As no ischaemic signs were observed, and the sac was sutured and reduced. Femoral hernioplasty was accomplished with polypropylene mesh. The postoperative course was uneventful and the patient was discharged within 24 hours. After an exhaustive literature review, we have found few cases reporting the presence of fallopian tube in adult women with femoral hernia, but none described a recurrent groin pain coinciding with menstruation, as in this case.